Bilateral midbrain transection induced hyperphagia accelerates the development of diabetes in Spontaneously Diabetic Torii (SDT) rats - Sasase, Tomohiko; Ito, Makoto; Ishii, Yukihito; Ohta, Takeshi (JSMARTech, 2021)
Spontaneously Diabetic Torii (SDT) rat is a model of severe type 2 diabetes and its complications. These characteristics of SDT rat are very useful to research diseases; however, the slow onset of diabetes may limit the usefulness of this animal model. To solve this problem, we performed bilateral midbrain transection on SDT rats and evaluated whether hyperphagia accelerates the onset of diabetes. By severing ascending fibers from the nucleus tractus solitarius to limbic regions through ventral and dorsal tegmental regions, food consumption was significantly increased in SDT rats and the onset of diabetes was accelerated. Cumulative incidence of diabetes in midbrain transected SDT rats was 88.9% at 7Â weeks after surgery (14Â weeks of age), while sham operated rats was 20.0%. Increased food consumption was correlated to body weight, plasma glucose level, plasma triglyceride level, and plasma insulin level. In conclusion, the overeating caused by blocking anorexigenic signal in brain significantly accelerates the onset of diabetes in SDT rats. The early development of type 2 diabetes may accelerate microvascular complications and is considered useful in the study of the disease in SDT rats.